Energy Harvesting Enabled Cooperative Networks: Resource Allocation Techniques, Protocol Design And Performance Analysis - Kehinde, Ojo Festus (2019)
In In wireless cooperative communication networks, cooperative relaying techniques can be employed to mitigate fading and attenuation problems by positioning relay nodes between a transmitter and a receiver. Therefore, network performance such as efficiency, throughput, and reliability can be improved. However, energy-constrained wireless cooperative relay nodes have a limited viable lifetime, which cannot sustain steady network connectivity, thereby making reliable communication difficult. Recently, energy harvesting (EH) via radio frequency (RF) signals appears to be a solution for sustaining the lifetime of the wireless cooperative relay nodes. In the past years, researchers have proposed some resource allocation techniques and protocols for simultaneous wireless information and power transfer (SWIPT) in the wireless cooperative communication networks. Nevertheless, there are still a lot of challenges being faced by the researchers to achieve an efficient SWIPT in such network. In this work, a new energy saving (ES) resource allocation technique is proposed for RF-EH enabled cooperative networks by adopting time switching relaying (TSR) and power splitting relaying (PSR) protocols. This is based on the assumption that the relay node uses a certain proportion of the harvested power in the current transmission block and then save the remaining portion for the next transmission block. Unlike the previous works, in that the resource allocation techniques in RF-EH enabled cooperative networks have been considered under the assumption that the energy-constrained relay must utilize all of its harvested power in each transmission block. The proposed ES technique is then optimized by considering the optimization problems. Then, the scenario of EH-enabled cooperative network with the presence of an interfering transmitter is considered. A hybridized power-time splitting based relaying (HPTSR) protocol is also proposed with amplified-and-forward (AF) and decode-and-forward (DF) relaying techniques by introducing a channel-based and power-time splitter into the relay receiver architecture are analyzed. Numerical results revealed that the proposed ES-TSR and ES-PSR protocols outperformed the existing TSR and PSR protocols with an energy efficiency gain of 13.87 % and 8.31 %, respectively, particularly, when the number of transmission block L=10. These results show that the proposed ES resource allocation technique is more energy efficient than the existing ones. At the optimal throughput value, the proposed AF HPTSR protocol outperformed the existing AF PSR, TSR, and time power switching relaying (TPSR) based protocols with a throughput gain of 54.18 %, 72.31 %, and 10.47 %, respectively. The proposed DF HPTSR protocol showed a performance gain of 2.81 % over the proposed AF HPTSR protocol. These results show that the proposed AF or DF HPTSR protocol can achieve a better throughput performance over the existing protocols, especially at high signal-to-noise ratio.